Arsenic, cadmium, mercury, and lead in imported pet food in Costa Rica - Naranjo-Jiménez, Carolina (2022)
Introduction. The intake of heavy metals can cause health problems in animals. Objective. To determine the concentration of cadmium, mercury, lead, and arsenic in 34 imported balanced foods marketed in Costa Rica for dogs, cats, rabbits, hamsters, turtles, and ornamental fish. Materials and methods. The content of arsenic (As), cadmium (Cd), mercury (Hg) and lead (Pb) in imported balanced foods for six pets was quantified during the months of May to October 2018. On a random basis, authorized feed stores were visited to purchased ten packages of dog and cat food, five for ornamental fish, four for turtles, three for hamsters, and two for rabbits. The samples were analyzed at the Animal Nutrition Research Center of the Universidad de Costa Rica using atomic absorption spectrophotometry with graphite tube atomizer (As, Cd, Pb) and quartz cells (Hg). Results. The concentrations obtained in the food for dogs and cats, adults and puppies, rabbits, hamsters, ornamental fish, and turtles were for As 0.009, 0.013, 0.003, non-detectable (ND), ND, 0.036, and 0.113 ppm, respectively; for Cd ND, 0.021, 0.022, 0.031, 0.010, 0.037, 0.139, and 0.043 ppm, respectively; for Hg 0.101, 0.078, 0.045, 0.040, 0.031, 0.045, 0.032, and 0.032 ppm, respectively, and for Pb of 0.381, 0.885, 0.573, 0.740, 0.446, 0.732, 0.763, and 0.841 ppm, respectively. Conclusions. The contents of heavy metals in pet foods did not exceed the maximum values allowed for their commercialization. This work increases the information available on the safety of food for ornamental fish, hamsters, turtles, and rabbits, also promotes continuous monitoring strategies, and the understanding of the real potential for accumulation in animals, and its effects on their welfare.